Positioning Pesantren as Community-Based Educational Brands: A Case Study Pesantren Nurul Ulum - Ramin, Moh (Molang: Journal Islamic Education, 2025)
Through a qualitative case study approach, this study examines Pesantren Nurul Ulum's positioning strategy as a community-based educational institution. The research focuses on how the pesantren builds its institutional identity not through formal promotion but through social involvement, collective narratives, and local values that live in the surrounding community. Data was collected through in-depth interviews, participatory observation, and document analysis from pesantren managers, santri guardians, and community leaders. Data analysis was done thematically and confirmed through triangulation of techniques and data sources. The results showed that Pesantren Nurul Ulum successfully positioned itself as an institution that blends socially and spiritually with the community, with legitimacy built through participation, cultural symbols, and alumni’s narratives. The branding strategy is organic and rooted in shared experiences, not merely institutional visualization or promotion. This finding strengthens the theoretical framework of community-based branding, which emphasizes the importance of sustainable social relationships in shaping institutional image. Pesantren faces serious challenges in managing digital communication, which is an important aspect in expanding its influence in the era of information technology. This research makes a theoretical contribution to the development of Islamic education branding discourse. It offers practical guidance for pesantren and similar institutions in building authentic, contextual, and socially relevant positioning strategies.